PRIVATE SECURITY SURVEILLANCE SYSTEM - BENJAMIN KOMMEY; SETH KOTEY; ERIC TUTU; DANIEL OPOKU (Journal of Engineering Studies and Research, 2021)
Security is an essential need for man. Without the sense of security, daily human activities will be greatly affected. Most people go to great lengths to ensure there is a presence of security in their environment, often employing dedicated personnel to keep watch over them and their property. This paper proposes a design of a microcontroller based electronic security system which helps to detect possible intruders to a home. This security system is designed to reduce the need of having personnel stationed as security guards over a home. It has the primary unit called the Area Watch Unit (AWU) consisting of a motion detection unit that effectively detects motion around specified perimeters which is then followed by a computer vision to identify and classify what caused the motion. A facial recognition algorithm is run on the face extracted from the image captured after the object that caused the motion is identified and classified as human. Access is then granted to the individual if the results from the facial recognition is positive otherwise a message is sent to the owner of the home indicating a possible intruder is present. There is also a Final Recovery Unit (FRU) which sends a message to the owner of the home and sounds an alarm whiles flashing lights in the event that the Area Watch Unit (AWU) is by-passed without authority.